Radial scar lesions of the breast diagnosed by needle core biopsy: analysis of cases containing occult malignancy. Issue 3 (26th May 2006) - Douglas-Jones, Anthony G; Denson, Jemimah L; Cox, Adam C; Harries, Iwan B; Stevens, Guy
Abstract : Aim: To identify and review cases of false negative needle core biopsy (NCB) in the preoperative investigation of radial scar/complex sclerosing lesion (RS/CSL) lesions—that is, benign NCB from RS/CSL which contained malignancy on excision. Methods and results: A total of 11 false negative NCB in RS/CSL lesions from 281 (3.9%) were identified (6 cases: B1, 2 cases: B2 and 3 cases: B3). In 6 of 11 cases a radial scar or stromal sclerosis was seen in NCB. Localisation biopsy showed duct carcinoma in situ in six cases, duct carcinoma in situ with invasive carcinoma in three and invasive carcinoma in two. In all 11 cases, needle tracks were identified as missing the malignant epithelium by a mean of 5 mm (median:4 mm; range:1–20 mm). In 9 of 11 cases, the malignancy was missed by <6 mm. Conclusions: Despite evidence of accurate targeting of lesions, the use of NCB instead of fine needle aspiration cytology has not eliminated the problem of false negative biopsy in RS/CSL, and excision is recommended.